Lower hypothalamus subunit volumes link with impaired long-term body weight gain after preterm birth - Ruzok, Tobias; Schmitz-Koep, Benita; Menegaux, Aurore; Eves, Robert; Daamen, Marcel; Boecker, Henning; Rieger-Fackeldey, Esther; Priller, Josef; Zimmer, Claus; Bartmann, Peter; Wolke, Dieter; Sorg, Christian; et al. (Frontiers in Endocrinology, 2022)
Introduction: Preterm birth is associated with an increased risk for impaired body weight gain. While it is known that in prematurity several somatic and environmental factors (e.g., endocrine factors, nutrition) modulate short- and long-term body weight gain, the contribution of potentially impaired body weight control in the brain remains elusive. We hypothesized that the structure of hypothalamic nuclei involved in body weight control is altered after preterm birth, with these alterations being associated with aberrant body weight development into adulthood. Materials and Methods: We assessed 101 very preterm (i.e., <32 weeks of gestational age) and/or very low birth weight (i.e., <1500g; VP/VLBW) and 110 full-term born (FT) adults of the population-based Bavarian Longitudinal Study with T1-weighted MRI, deep learning-based hypothalamus subunit segmentation, and multiple body weight assessments from birth into adulthood. Results: Volumes of the whole hypothalamus and hypothalamus subunits relevant for body weight control were reduced in VP/VLBW adults and associated with birth variables (i.e., gestational age and intensity of neonatal treatment), body weight (i.e., weight at birth and adulthood), and body weight trajectories (i.e., trajectory slopes and cluster/types such as long-term catch-up growth). Particularly, VP/VLBW subgroups, whose individuals showed catch-up growth and/or were small for gestational age, were mostly associated with volumes of distinct hypothalamus subunits such as lateral or infundibular/ventromedial hypothalamus. Conclusion: Results demonstrate lower volumes of body weight control-related hypothalamus subunits after preterm birth that link with long-term body weight gain. Data suggest postnatal development of body weight -related hypothalamic nuclei in VP/VLBW individuals that corresponds with distinct body weight trajectories into adulthood.